Arsenic in framboidal pyrite from recent sediments of a shallow water lagoon of the Baltic Sea. Issue 6 (19th April 2013) - Neumann, Thomas; Scholz, Florian; Kramar, Utz; Ostermaier, Michael; Rausch, Nicole; Berner, Zsolt
Abstract: Arsenic is a redox‐sensitive element of environmental relevance and often enriched in iron sulphides. Because sediments from the Achterwasser lagoon, a part of the estuarine system of the river Oder, south‐west Baltic Sea, show unexpectedly high pyrite concentrations of up to 7·5 wt% they were used to investigate the influence of authigenic pyrite on the mobility and burial of As in the coastal environment. Micro‐X‐ray‐fluorescence measurements of 106 micrometre‐sized pyrite framboids from the anoxic sediments show highly variable As concentrations ranging from 6 to 1142 μg g −1 . Even within a 1 cm thick layer, the As concentration of different framboids varies greatly and no clear depth trend is visible throughout the 50 cm long sediment core. Pyrite can account for 9 to 55% (average 22%) of the total As budget of the sediments and the degree of trace metalloid pyritization for As ranges from 26 to 61%, indicating that authigenic pyrite formation is an important process in the geochemical cycling of As in coastal sediments. High‐resolution micro‐X‐ray fluorescence mapping of single pyrite grains shows that As is distributed inhomogeneously within larger framboids, suggesting changing pore water composition during pyrite growth. X‐ray absorption near edge structure spectra indicate that As is usually present as As(‐I) substituting S in the pyrite lattice. However, in samples close to the sediment/water interface a considerable part of As is in higher valence states (+III/+V). This can be explained by frequent re‐suspension of the surficial sediments to the oxic water column due to wave action and subsequent re‐deposition, leading to the adsorption of As oxyanions onto pyrite. Although reduced As(‐I) becomes more important in the deeper samples, reflecting decreasing redox potential and a longer time since deposition, the occurrence of oxidized As species (AsIII/AsV) in pyrite in the anoxic part of the sediment suggests formation under dysoxic conditions.